Croire et soutenir dans une économie morale de la suspicion - Grégory Beltran (Recherches Sociologiques et Anthropologiques)
In France, asylum applications are subject to a culture of suspicion that systematically calls into question the veracity and credibility of applicants’ stories. Taking an interest in LGBTI asylum, i.e. requests for protection from people exiled because of their sexual orientation or gender identity, highlights both the fragility of the criteria – institutional and associative – for authenticating these accounts and the strength of this policy of suspicion, which influences even the forms of support. The aim of this research is to shift the focus from the construction of the category of “lying” and the verification mechanisms of asylum institutions to the effects of this category on support practices for LGBTI exiles. The article presents the methods of verification and the expectations of asylum institutions, particularly with regard to proof of homosexuality and transidentity. It goes on to analyse the complex relationship that actors in the field of support for exiles have with this category of “lying” redefined by the asylum administration, depending in particular on their political and moral positioning in this field.